Determination of trace metals in air of Chittagong city-Bangladesh - Ahmed, Mohammed Jamaluddin; Ali, Mohammed Khorshed; Hossain, Muzammel; Siraj, Shajahan; Ahsan, Mohammed Aminul (European Journal of Chemistry, 2012)
Air pollution problem is severe in the urban areas caused by both mobile as well as stationary sources. Mainly the two-stroke and diesel-run vehicles cause the severity of the problem by emitting highly contaminated exhausts. Considering severity of the problem, current study was undertaken to measure the air pollutants level in air of Chittagong city, Bangladesh. The heavy metals Zn, Pb, Mn, Cd, Cu and Co in suspended particulate matter (SPM) were determined at different locations of Chittagong city. The sampling locations were selected to reflect different influences from industrial and mobile sources in the highly populated center part of Chittagong city. Samplings were done during October and November 2008 from different areas of the metropolitan city of Chittagong city (Newmarket, Bahaddarhat, Nasirabad, General Electric Company (G.E.C.) Circle and Director’s Office of Department of Environment, Bangladesh). High volume sampler was used for the determination of SPM and the different metal concentrations were measured by atomic absorption spectrophotometer (AAS). The average results of particulate matters and trace metals have been compared to national and international standards. The value of SPM in air of Chittagong city is higher than that of Threshold Limit Value (TLV) recommended by World Health Organization (WHO), Environmental Protection Agency (EPA), USA and Department of Environment (DoE), Bangladesh. The metal concentrations of ambient air collected at different locations in Chittagong city is exceeded the threshold limit values and as a result the air of Chittagong city is considered polluted. Therefore, it is suggested that Government of Bangladesh should take proper steps to control the air pollution of Chittagong city.